Inclusion compound of Fosinopril with β-cyclodextrin. Issue 1 (2009) - Bratu Bratu, I. I.; Kacso Kacso, Irina Irina; Borodi Borodi, Gh. Gh.; Constantinescu Constantinescu, Daniela E. Daniela E.; Dragan Dragan, Felicia Felicia
Abstract : Solid state interactions of bioactive substance (4-cyclohexyl-1-[2-[(2-methyl-1-propanoyloxy-propoxy)-(4-phenylbutyl)phosphoryl]acetyl]-pyrrolidine-2-carboxylic acid, called Fosinopril), with β -cyclodextrin ( β -CD), the so-called inclusion compounds of a bioactive (cardiovascular) drug is obtained by different preparation methods: kneading, co-precipitation and freeze-drying. The so obtained compounds were investigated by FTIR spectroscopy, X-ray diffraction method, and differential scanning calorimetric measurements (DSC) to evidence their formation. X-ray diffraction patterns show that the inclusion compound was obtained for kneaded, co-precipitation and freeze-dried products. The crystalline/amorphous degree for these compounds was also investigated. Molecular modeling (MM+ molecular mechanics) shows the spatial architecture of the inclusion compound in good agreement with FTIR experimental data: the drug is included with the propanoyloxy-propoxy group inside β -cyclodextrin cavity. These findings may constitute a direct contribution to the molecular encapsulation of Fosinopril into β -cyclodextrin, improving Fosinopril stability and bioavailability of the drug, also.